2020
DOI: 10.3390/en13133497
|View full text |Cite
|
Sign up to set email alerts
|

Buildings Energy Efficiency Analysis and Classification Using Various Machine Learning Technique Classifiers

Abstract: Energy efficiency is a major concern to achieve sustainability in modern society. Smart cities sustainability depends on the availability of energy-efficient infrastructures and services. Buildings compose most of the city, and they are responsible for most of the energy consumption and emissions to the atmosphere (40%). Smart cities need smart buildings to achieve sustainability goals. Building’s thermal modeling is essential to face the energy efficiency race. In this paper, we show how ICT and data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Optimal integration and other economic considerations like hydrogen-based energy storage systems were discussed by Serra et al [35]. Benavente-Peces et al [38] analysed energy efficiency and classification of energy usage in various sectors. Revenues and impacts of invest-ment costs were discussed by Zhang et al [42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal integration and other economic considerations like hydrogen-based energy storage systems were discussed by Serra et al [35]. Benavente-Peces et al [38] analysed energy efficiency and classification of energy usage in various sectors. Revenues and impacts of invest-ment costs were discussed by Zhang et al [42].…”
Section: Methodsmentioning
confidence: 99%
“…To ensure energy security is the first aim of the 2016 IEP, to make sure that South Africa is not short of energy supply within the time frame [37]. To achieve this target, broader consultations were made between the energy and the economic sectors, such as commerce, transport, industry, agriculture, and residential [38]. Each sector was mandated to provide the policy planners with a breakdown of energy consumed in 2010 on cooling, heating, pumping, petrol, electricity, gas, and coal.…”
Section: Demand and Supply Energy Forecast And Analysis 91 Demandmentioning
confidence: 99%
“…As a result, improvement in the insulation properties of all the components of the building envelope will result in both increased comfort of the indoor thermal environment and improved energy efficiency levels for rural residential buildings during the winter season. The energy efficiency levels can be further examined using machine learning techniques [54].…”
Section: Improvements Of Energy Efficiency Standardsmentioning
confidence: 99%
“…These results indicate that air-conditioning and lighting sockets in public buildings play an important role in building energy consumption, of which operation characteristics are worthy of special attention. Benavente-Peces et al used various machine learning technique classifiers to analyze and classify building energy efficiency, and they demonstrated that reliable classification is feasible with a few featured parameters [6]. Suzane A. Monteiro et al developed a methodology of energy efficiency for lighting and air-conditioning systems in buildings using a multi-objective optimization algorithm [7].…”
Section: Introductionmentioning
confidence: 99%
“…From the literature [1][2][3][4][5][6][7], we can discover the necessity of building energy efficiency, especially for public buildings. Therefore, how to use energy consumption data in monitoring platform is important, such as studying human behavior for an energy retrofit shown in the literature [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%